“Evaluación de la política pública en materia de fortalecimiento de la actividad turística en los niveles de gobierno local de la provincia de Zamora Chinchipe” - Olmedo Escobar, Diego Orlando (2024)
The "Public Policy Evaluation for the Strengthening of Tourism Activity at Different Levels of Local Government in the Province of Zamora Chinchipe" is an analysis of the tourism sector in this Ecuadorian region. The study examines how public policies influence tourism development and their effectiveness across various levels of local government. It investigates the allocation of resources, governance structure, and the perceptions of stakeholders involved in tourism, including local governments, tourism entrepreneurs, and tourists. The research employs a mixed-methods approach, combining qualitative and quantitative analyses, to gain a comprehensive view of the current state of tourism and the effectiveness of implemented public policies. Surveys and interviews were conducted to collect primary data and understand the experiences and opinions of key sector players. The findings of this study aim to provide a solid foundation for informed decision-making and continuous improvement in local tourism management. It seeks to identify areas of strength, as well as challenges and opportunities for tourism development in Zamora Chinchipe, with the aim of proposing recommendations that contribute to sustainable and responsible sector growth. This study is crucial for understanding the dynamics of tourism in a regional context and how public policies can be better focused to maximize their positive impact on the economy, culture, and environment. The research contributes to the knowledge of tourism in Ecuador and offers valuable insights for similar contexts, contributing to the development of more effective and sustainable tourism strategies. Collaboration among different levels of government and sector stakeholders is fundamental to the success of these policies, and the study underscores the importance of this synergy for the future of tourism in the province.